CHEMORADIATION AND ANTI-PD-1 THERAPY FOR RECTAL CANCER IN A PATIENT WITH MULTIPLE PRIMARY TUMORS: A RARE CLINICAL CASE - M. Bobkov (Clinical Medicine and Pharmacology, 2026)
The article presents a rare clinical case of a 69-year-old patient with three multi-ple primary malignant tumors: cutaneous melanoma (pT4aN2bM0, stage IIIb), synchronous left renal cell carcinoma (cT2N0M0, stage II), and low-ampullary rectal cancer (cT2N0M0, stage I, pMMR/MSS). Treatment with the PD-1 inhibi-tor prolgolimab resulted in complete regression of metastatic melanoma lesions and stabilization of renal cancer. Upon development of rectal cancer, neoadjuvant chemoradiotherapy with capecitabine was initiated. Due to organizational limita-tions of the compulsory health insurance system (inability to administer both therapies simultaneously within a single hospitalization), a forced sequential reg-imen was applied: chemoradiotherapy is interrupted every 2 weeks for prolgo-limab administration. Drawing on data from the PACIFIC-2 trial and the net-work meta-analysis by Baek et al. (2026), the authors argue that sequential im-munotherapy after radiotherapy may represent not a compromise but a poten-tially more effective strategy, supported by biological rationale (immunogenic cell death, cross-priming, overcoming adaptive resistance). This case demonstrates the efficacy of prolgolimab in synchronous melanoma and renal cancer, as well as the potential of incorporating PD-1 inhibitors into total neoadjuvant therapy for rectal cancer. The authors conclude that comprehensive DRG tariffs for com-bined therapy are needed.